Repair of stone masonry arch bridges - Oliveira, Daniel V. (2004)
This paper deals with the analysis and design of repair measures concerning two Portuguese masonry arch bridges, carried out at University of Minho. The first example is related with a masonry bridge built in the 19th century, composed of six pointed stone arches and located in the center of Portugal. The second example is a medieval masonry bridge composed of three semicircular stone arches and located in the North of Portugal. Repair measures adopted to re-establish the safety of the bridges are described. These measures were conceived in order to respect the modern principles of structural intervention in architectural heritage.